2019
DOI: 10.3390/ma12213549
|View full text |Cite
|
Sign up to set email alerts
|

Spark Plasma Sintering Behavior of Nb-Mo-Si Alloy Powders Fabricated by Hydrogenation-Dehydrogenation Method

Abstract: In this study, the sintering behaviors of Nb-6Mo-20Si-3Cr (at percentage) in situ composite powders were studied. The Nb alloy powder was fabricated by a hydrogenation-dehydrogenation method, and both the alloy ingot and powders consisted of two phases: An Nb metal phase and the α-Nb5Si3 phase. Consolidation of the alloy powders was performed at 1500, 1600, and 1700 °C using spark plasma sintering, and the microstructures and phases formed at various sintering temperatures were analyzed. Micropores were observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…We compared the results in this study with previous study [24]. They found that no oxide was observed in the microstructure of sintered compacts even when the Nb-6Mo-20Si-3Cr (at.-%) alloy powders were produced via the HDH method and consolidated using SPS.…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…We compared the results in this study with previous study [24]. They found that no oxide was observed in the microstructure of sintered compacts even when the Nb-6Mo-20Si-3Cr (at.-%) alloy powders were produced via the HDH method and consolidated using SPS.…”
Section: Resultsmentioning
confidence: 81%
“…Nb is one such element that forms a hydride during hydrogen annealing, making it brittle and easier to pulverise. Park et al [23,24] used this property of Nb and produced Nb-Mo-Si silicide-based alloy powders via the HDH method. Based on these studies and the results of the present study in Figure 3, it would be possible to produce Nb alloy powders of various compositions using the HDH method.…”
Section: Resultsmentioning
confidence: 99%
“…The aforementioned metallic UHTMs can be single-phase or multiphase materials. The RMICs are multiphase materials with microstructures that consist of bcc solid solution(s) and intermetallic(s) [1,2,[20][21][22][23][24][25][26][27][28], whereas the RHEAs and RCCAs can be single-phase bcc solid solution alloys or multiphase alloys with microstructures that consist of solid solution(s) and intermetallic(s), e.g., [3], or only intermetallics, e.g., [15,16]. For the said categories of metallic UHTMs, the M 5 Si 3 silicides (M = transition metal (TM), RM), in particular the Nb 5 Si 3 and Mo 5 Si 3 silicides, have attracted the interest of alloy designers and developers [1,3,13,24] owing to their creep properties and high Si content that benefits oxidation resistance [29][30][31][32][33][34][35][36][37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%